IMPLEMENTASI ADMINISTRATIF: KAPASITAS SUMBER DAYA MANUSIA SATUAN POLISI PAMONG PRAJA DALAM MELAKUKAN PEMBINAAN DAN PENYULUHAN PADA PEDAGANG KAKI LIMA - Septi Diah Utami; Subur Bahri; Hary Priyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas 17 Agustus 1945 Banyuwangi, 2021)
Abstract: Administrative Implementation: Human Resources Capasity Of Pamong Praja In Doing Couching And Counseling On Street Vendor . In an effort to respond to the aspirations of street vendors (PKL) to meet their needs, a system of guidance and counseling is needed that is formed on the orders and public trust. The Civil Service Police Unit (Satpol PP) is one of the institutions that provide services to street vendors, and plays an important role in efforts to prevent and overcome violations of local regulations by street vendors, because the Satpol PP has the power of outhority. The services provided by the Satpol PP to the street vendors will shape the trustworthiness of street vendors against the government. However, the linear lack of competence of the implementers at the Satpol PP will affect the service of the bureaucracy in implementing good governance. This journal is to describe the capacity of human resources at the Satpol PP in an effort to carry out coaching and counseling. Data analysis was carried out by qualitative methods with a descriptive-analysis approach based on the public policy perspective used and to analyze the literature. The results of the analysis state that the development of the capacity of human resources in the Satpol PP needs to be adjusted to its scientific competencies which are carried out systematically.